2020
DOI: 10.1371/journal.pntd.0008590
|View full text |Cite
|
Sign up to set email alerts
|

Genomic loss in environmental and isogenic morphotype isolates of Burkholderia pseudomallei is associated with intracellular survival and plaque-forming efficiency

Abstract: Background Burkholderia pseudomallei is an environmental bacterium that causes melioidosis. A facultative intracellular pathogen, B. pseudomallei can induce multinucleated giant cells (MNGCs) leading to plaque formation in vitro. B. pseudomallei can switch colony morphotypes under stress conditions. In addition, different isolates have been reported to have varying virulence in vivo, but genomic evolution and the relationship with plaque formation is poorly understood. Methodology/Principle findings To gain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Of those, the deleted genes are including genes involved in T3SS-3 and T6SS-5 systems. Interestingly, Saiprom et al (2020) also identified an absence of multiple T3SS-1 genes of previously described Thai environmental strain RF80.…”
Section: Genetic Structural or Molecular Variations Observed In Hostmentioning
confidence: 63%
“…Of those, the deleted genes are including genes involved in T3SS-3 and T6SS-5 systems. Interestingly, Saiprom et al (2020) also identified an absence of multiple T3SS-1 genes of previously described Thai environmental strain RF80.…”
Section: Genetic Structural or Molecular Variations Observed In Hostmentioning
confidence: 63%
“…Although the function of cell-to-cell fusion in the pathogenesis of melioidosis is not yet well-determined, B. pseudomallei is capable of inducing MNGC in lung tissue of melioidosis patients and infected mice ( Wong et al, 1995 ; Conejero et al, 2011 ). In addition, deletion of T6SS-5 genes drastically decreased intracellular replication, cell-to-cell fusion, and virulence of B. pseudomallei in mammalian models of acute infection ( Pilatz et al, 2006 ; Burtnick et al, 2011 ; French et al, 2011 ; Hopf et al, 2014 ; Schwarz et al, 2014 ; Toesca et al, 2014 ; Saiprom et al, 2020 ). Thus, it is possible that the dramatic within-host adaptive changes in intracellular replication and cell-to-cell fusion may enhance the virulence in vivo , which could influence the outcome of P17.…”
Section: Discussionmentioning
confidence: 99%
“…An intracellular bacterial survival assay was performed to compare the ability of B. pseudomallei pairs to grow within the host cells. The assay was performed in two independent experiments as previously described ( Saiprom et al, 2020 ), but with some modifications. Briefly, A549 cells were seeded at 1.5 × 10 4 cells per well into a 96-well plate, washed with PBS, and infected with B. pseudomallei at MOI of 30:1 as described in the MNGC assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…were resuspended in 2 mL of PBS and adjusted to a 0.5 McFarland standard solution. Fluorescent staining was performed as previously described with modifications [ 25 ]. Briefly, A549 cells suspended in RPMI containing 1% FBS were seeded at 5 × 10 5 cells/well on a sterile glass coverslip placed in a 6-well tissue culture plate and incubated overnight at 37 °C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%